STUDI IDENTITAS REGIONAL UNTUK PARIWISATA BERKELANJUTAN DI KECAMATAN X KOTO KABUPATEN TANAH DATAR - Rachmi, Mita Anisyah (STKIP PGRI Sumbar, 2014)
This Research aim to know, explaining and analysing Identity Regional For the Tourism of hContinuation in District Of X Koto. Problems which studied in this research is : (1) How identity ofregional for the tourism of have continuation to seen from natural resources potency in District of X Koto,(2) How identity of regional for the tourism of have continuation to seen from cultural resource potencyin District Of X Koto Kabupaten Tanah Datar. This Research represent research have the character ofdescriptive qualitative. Research Subjek taken with technique of snowball. Research location in NewKenagarian Koto Baru and Kenagarian Pandai Sikek District Of X Koto Kabupaten Tanah Datar.Technique data collecting the used is observation, interview, and documentation. Pursuant to result ofresearch in field indicate that in District of X Koto have resource potency which divided in two potencythat is natural resources potency and cultural resource potency. Potency natural resources that is Mountnatural beauty of Marapi and Mount of Singgalang, while cultural resource potency is application in theform of handicraft that is Clever weave cloth of Sikek. the Potency Resource represent identity orindividuality of regional able to support tourism have continuation. Mount of Marapi have fascination inthe form of natural beauty so that can support tourism have continuation need involvement of society andgovernment. Governmental participation there have, while from society still less. Mount of Singgalangowning natural beauty to be can support tourism have continuation need involvement of society andgovernment. Participation of government still there is no and from society also still less. Weave clothhave fascination yield cloth with unique motif, so that can support tourism have continuation to neededinvolvement of society and government.